2013
DOI: 10.1097/bsd.0b013e31828bc02f
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Range of Motion After Single-level Discover Cervical Artificial Disk Replacement

Abstract: This study demonstrated that the single-level Discover CADR increased the ROM of the treated segment and the adjacent segments. There was also an increase in the global ROM and the total neck motion in the sagittal and the coronal planes, although there was no significant difference in the horizontal plane before and after operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Most patients in this study cohort showed preserved or increased ROM at final follow-up. Chen et al reported not only an increase in ROM at the treated segment after CDA but also an increase in ROM in the adjacent segments [14].…”
Section: Discussionmentioning
confidence: 98%
“…Most patients in this study cohort showed preserved or increased ROM at final follow-up. Chen et al reported not only an increase in ROM at the treated segment after CDA but also an increase in ROM in the adjacent segments [14].…”
Section: Discussionmentioning
confidence: 98%
“…The design of the most commonly used TCDA implies large kinematic differences among the different implants. Although all of these devices globally preserve segmental motion at the cervical spine, each prosthesis design has different restriction patterns [9][10][11][12][13][14]. This particularity might have an influence on the clinical outcomes of the different devices.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies of in vivo motion assessment after cervical disc arthroplasty have been limited to measuring the range of motion from static lateral radiographs taken at the extremes of full flexion and extension ( 1 - 3 ). Range of motion is important, but it fails to characterise the mid-range motion where the majority of daily living activities take place.…”
Section: Introductionmentioning
confidence: 99%